Comparison of three aids for teaching lumbar surgical anatomy. (August 2013) - Das, S.; Mitchell, P.
Abstract: Reduced surgeons' training time has resulted in a need to increase the speed of learning. Currently, anatomy education involves traditional (textbooks, physical models, cadaveric dissection/prosection) and recent (electronic) techniques. As yet there are no available data comparing their performance. The performance of three anatomical training aids at teaching the surgical anatomy of the lumbar spinal was compared. The aids used were paper-based images, a three-dimensional plastic model and a semitransparent computer model. Fifty one study subjects were recruited from a population of junior doctors, nurses, medical and nursing students. Three study groups were created which differed in the order of presenting the aids. For each subject, spinal anatomy was revised by the investigator, teaching them the anatomy using each aid. They were specifically taught the locations of the intervertebral disc, pedicles and nerve roots in the lateral recesses. They then drew these structures on a response sheet (three response sheets per subject). The computer model was the best at allowing subjects accurately to determine structure location followed by the paper-based images, the plastic model was the worst. Accuracy improved with successive models used but this trend was not significant. Subjects were not versed in spinal anatomy beforehand, so meaningful baseline measures were not available. The educational performance of surgical anatomical training aids can be measured and compared. A computer generated 3 dimensional model gave the best results with paper-based images second and the plastic model third.